2016
DOI: 10.1002/cne.24011
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral cortical inputs to the rostral and caudal motor areas in rats

Abstract: Rats have a complete body representation in the primary motor cortex (M1). Rostrally there are additional representations of the forelimb and whiskers, called the rostral forelimb area (RFA) and the rostral whisker area (RWA). Recently we showed that sources of thalamic inputs to RFA and RWA are similar, but they are different from those for the caudal forelimb area (CFA) and the caudal whisker area (CWA) of M1 (Mohammed and Jain [2014] J Comp Neurol 522:528-545). We proposed that RWA and RFA are part of a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In rodents, two frontal cortical regions are critically involved in controlling the contralateral forelimb: the rostral forelimb area (RFA) and the caudal forelimb area (CFA). They have been identified by electrical 17 20 and optogenetic microstimulation 21 , 22 , as well as by anatomical tracings 23 25 , yet their respective functional role is still unclear. It has been speculated that they are organized in an analogous way to the primate frontal cortex 17 , 19 , 23 , 26 28 with CFA as the primary motor cortex and RFA as a premotor area.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, two frontal cortical regions are critically involved in controlling the contralateral forelimb: the rostral forelimb area (RFA) and the caudal forelimb area (CFA). They have been identified by electrical 17 20 and optogenetic microstimulation 21 , 22 , as well as by anatomical tracings 23 25 , yet their respective functional role is still unclear. It has been speculated that they are organized in an analogous way to the primate frontal cortex 17 , 19 , 23 , 26 28 with CFA as the primary motor cortex and RFA as a premotor area.…”
Section: Introductionmentioning
confidence: 99%
“…To model a relevant system in vivo, the rostral forelimb area (RFA), a premotor area, was used for neural recordings while either closed-loop ADS or random stimulation (RS) was delivered to somatosensory cortex (S1), either in the S1 forelimb area (S1FL) or the S1 barrel field (S1BF). These areas share reciprocal neuroanatomical connections, providing an anatomical framework for changing synaptic efficacy [29]. In a previous study, we found that an ADS protocol in a chronic injury model, i.e., pairing the occurrence of spikes in RFA with ICMS applied to S1, led to increased firing within RFA over a period of several days [28].…”
Section: Introductionmentioning
confidence: 87%
“…CFA, which reorganizes during skilled motor learning [17], exhibits significantly greater input from the primary somatosensory cortex and less from the secondary somatosensory cortex than RFA (Fig. 4) [10]. Physiological studies in the rat also suggest that RFA lacks sensory inputs, in contrast to CFA [155].…”
Section: Intracortical Circuits In the Sensorimotor Cortexmentioning
confidence: 98%
“…Motor intrinsic connections dictate the selection of movement-related muscle synergies through functional linking of motor cortical points, lateral inhibition of competing output, and shaping of representational borders [130][131][132][133][134]. Physiological and anatomical studies have illuminated the extensive intrinsic connections within the primary motor cortex [6][7][8] as well as the intracortical connections to higher motor areas [135][136][137], somatosensory cortex [10,138,139], and other cortical areas involved in motor control and spatial awareness (i.e., posterior parietal cortex, prefrontal cortex, and retrosplenial cortex) [10,[139][140][141][142]. Horizontal circuits interconnect neurons in the cortical columns within and across cortical regions, comprising a network of horizontally projecting axons in layers 2/3 and 5 [143,144].…”
Section: Intracortical Circuits In the Sensorimotor Cortexmentioning
confidence: 99%
See 1 more Smart Citation